Electrical conductivity of lithium montmorillonite (LiMMT) filled polymer-clay nanocomposites (PCNs) - Diamante, Junierose C. (2012)
Conducting polymer-clay nanocomposites (PCNs) have potential battery applications as solid polymer electrolytes and electrode materials, which require an electrical conductivity of around 10-3 S/cm. Lithium montmorilloniyr (LiMMT) with 4,400 µg/g lithium ions was prepared using the ion exchange process. Solution intercalation method was then used to prepare LiMMT-filled polyacrylonitrile (PAN) and polyaniline (PAni) matrix nanocomposites. Based from X-ray Diffraction (XRD) results, the PAN-based PCNs with 5 wt% LiMMT exhibited an intercalated microstructure between the polymer matrix and the LiMMT filler wwhile the filler in the 15 wt% LiMMTfilm formed an agglomerated microstructure. In the LiMMT-PAni films, the nanoclay was found to be having an agglomerated microstructure remained at 5 wt% and 15 wt%. Differential Scanning Calorimetry (DSC) results have shown that the glass transition temperature (Tg) increased with increasing LiMMT but decreased with an increase in film thickness. Results from linear sweep voltammetry at four (4) volts showed that the conductivity of PAN-based films increased from 2.51 x 10-11 S/cm to 3.76 x 10-10 S/cm for the 50 µm-thick films, which is a 1300% increase in conductivity and from 1.08 x 10-10 S/cm to 8.73 x 10-9 S/cm for the 150 µm-thick, a 7900% increase in conductivity with increasing LiMMT. Although the electrical conductivities obtained are still below the required values for the application, the study has shown that it is possible to produce lithium-modified MMT, which can be used to increase the electrical conductivity of an intrinsically non-conducting polymer.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines, Diliman
Keywords: Lithium cells; Lithium montmorillonite (LiMMT).; Polymer-clay nanocomposites (PCNs).